Biplanar Fluoroscopy in Pediatric Orthopaedics. Issue 2 (June 2021) - Young, Porter; Rhea, Evan; Rasmussen, Luke; Loveless, Eric
Abstract : Biplanar fluoroscopy allows for the simultaneous acquisition of x-ray images in 2 planes without needing to move the extremity or C-arm. It is advantageous in cases such as pinning supracondylar humerus fractures or slipped capital femoral epiphyses where frequently alternating between 2 planes under fluoroscopic imaging is required. However, literature describing the technique is lacking. Therefore, the purpose of our article is to discuss room setup, advantages, and disadvantages of using biplanar fluoroscopy in cases involving the elbow, shoulder, hip, and knee.